The Influence of Si3N4w Volume Fraction on the Microstructure and Properties of Si3N4w/Si3N4 Composites via CVI Technique - Chen, Chao; Liu, Yongsheng; Yue, Wei; Ye, Fang; Wang, Jing; Zeng, Qingfeng (Frontiers in Materials, 2020)
Wave-transparent ceramic composites with excellent comprehensive performances are of particular significance for the development of space vehicles. In this study, Si3N4w was prepared by the gel-casting process and then combined with chemical vapor infiltration (CVI)-obtained Si3N4 to yield Si3N4w/Si3N4 composites with five Si3N4w volume fractions. The influence of the Si3N4w volume fraction on the microstructures, mechanical properties, and dielectric characteristics of the Si3N4w/Si3N4 composites were all studied. The results showed that Si3N4w/Si3N4 composites possess A sandwich structures. Higher Si3N4w volume fractions led to less incorporated amounts of the Si3N4 matrix at the same depth. The 25 vol% Si3N4w/Si3N4 composites integrated relatively higher Si3N4w volume fraction and load transfer ability of the matrix, leading to better flexural strengths reaching up to 41.37 MPa. The dielectric constants of the five prepared Si3N4w/Si3N4 composites ranged from 2.25 to 4.0. The dielectric losses were all lower than 0.005, demonstrating the good dielectric properties of the Si3N4w/Si3N4 composites.